A Discussion on the Research Methodology for Building a Gender-Responsive and Inclusive Education System in a Fragile and Conflict Affected Setting: A Case of the Democratic Republic of Congo - ZAGABE, Sanders (Journal of Research in Educational Sciences; Vol 14 No 16 (2023): JRES, Volume XIV, Issue 16, Winter 2023, 2023)
It is widely agreed that gender equality has a huge impact on sustainable economic growth. However, the gap in gender equality is getting larger because of global challenges we are facing creating room for more context-adapted research. Indeed, the fragile and conflicting settings are unique in the way that people perceive life and each other. Furthermore, most research made in this kind of setting is not specific to solving the problems related to the education sector in this context. The uniqueness of the D.R. Congo comes from the fact that the education system has been run by the private sector since its very beginning. Thus, the success of research for inclusive and safe schools for marginalized populations cannot be possible without including a variety of bodies, starting from government to religious organizations, and not leaving behind international organizations and other private entities. To cope with this singularity, the study must apply documentary, survey, longitudinal, cross-sectional, and trend methodology. This methodology will allow the study to dig deep into the beliefs, culture, and habits that make school inaccessible to marginalized people. The method used in writing the article is an analysis of the English and Polish literature on the subject.